СОНГУУЛИЙН КАМПАНИЙН ҮЕ ДЭХ УЛС ТӨРИЙН НАМУУД, НЭР ДЭВШИГЧДИЙН ХАРИУЦЛАГА - Д.Оюунчимэг (Politology, 2023)
The issue of election campaigning and its affects on electorates’ political consciousness and culture should not be stayed out of consideration. Political party and election platforms, financing of election campaignings and, methods, techniques and their results of political advertisement will be revised within the frame of article.